1989
DOI: 10.1002/1097-4679(198907)45:4<553::aid-jclp2270450409>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Replicated item level factor structure of the MMPI: Racial and sexual differences

Abstract: Item‐level factor studies of the MMPI date back to the work of Comrey (1957). Surprisingly, there are no extant studies of the items that clinicians use most in the course of daily MMPI interpretive reporting, namely, the 399 × 399 matrix that represents all of the items that comprise the traditional clinical and validity scales. Furthermore, there are no prior studies with adequate Ns that have examined the replicability of MMPI factor structure via available factor comparison techniques (Harman, 1976). In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…ality, there have been few studies examining the similarity in factorial structure for various racial and ethnic groups. Bernstein, Teng, Grannemann, and Garbin (1987) used a principal-components analysis with a large sample of Black, Hispanic, Native American, and White respondents and reported an invariant structure across all four groups; however, Beck et al (1989) found different factor structures for Black and White inpatients.…”
Section: Social Introversionmentioning
confidence: 99%
“…ality, there have been few studies examining the similarity in factorial structure for various racial and ethnic groups. Bernstein, Teng, Grannemann, and Garbin (1987) used a principal-components analysis with a large sample of Black, Hispanic, Native American, and White respondents and reported an invariant structure across all four groups; however, Beck et al (1989) found different factor structures for Black and White inpatients.…”
Section: Social Introversionmentioning
confidence: 99%
“…For example, Bernstein, Teng, Grannemann, and Garbein (1987) observed the principal-component structure of the MMPI across racial groups and found consistent patterns. In contrast, differences in factor structure were obtained across race by Beck and his associates (Beck et al, 1989) in a study that investigated item-level factor structure of the MMPI. Factors replicating poorly across race in the seven-factor solution included Psychoticism, Optimism, and Family Report (occurring only for Whites) as well as Paranoia (which occurred only for African Americans).…”
mentioning
confidence: 98%